Methyl 2,2-dimethoxy-8-oxo-1-oxaspiro[4.5]deca-6,9-diene-3-carboxylate - Lou, Yongbing (International Union of Crystallography, 2012)
In the title molecule, C(13)H(16)O(6), the cyclohexa-1,4-diene ring adopts a flat boat conformation (r.m.s. deviation from planarity = 0.060 Å) and the five-membered tetrahydrofuran ring adopts an envelope conformation with the carboxyl group-substituted C atom as the flap. The dihedral angle at the spiro junction is 89.1 (1)°. In the crystal, molecules are linked through weak C—H⋯O and van der Waals interactions.